Long‐range wireless sensor networks with transmit‐only nodes and software‐defined receivers. Issue 17 (3rd October 2011) - Huebner, Christof; Cardell‐Oliver, Rachel; Hanelt, Stefan; Wagenknecht, Tino; Monsalve, Alvaro
ABSTRACT: Wireless sensor networks for environmental monitoring and agricultural applications often face Long‐range requirements at low bit rates together with a large numbers of nodes. This paper presents the design and test of a novel wireless sensor network that combines a large radio range with very low power consumption and cost. Our asymmetric sensor network uses ultra‐low‐cost 40‐MHz transmitters and a sensitive software‐defined radio receiver with multi‐channel capability. Experimental radio range measurements in two different outdoor environments demonstrate a single‐hop range of up to 1.8 km. A theoretical model for radio propagation at 40 MHz in outdoor environments is proposed and validated with the experimental measurements. The reliability and fidelity of network communication over longer periods is evaluated with a deployment for distributed temperature measurements. Our results demonstrate the feasibility of the transmit‐only low‐frequency system design approach for future environmental sensor networks. Although there have been several papers proposing the theoretical benefits of this approach, to the best of our knowledge, this is the first paper to provide experimental validation of such claims. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : Low‐cost and low‐power 40‐MHz transmitters together with a sensitive software‐defined radio receiver form a multichannel single‐hop wireless network with range up to 1.8 km and high reliability. A theoretical model for radio propagation at 40 MHz in outdoor environments is proposed and validated with experimental measurements. Target applications are environmental monitoring and precision agriculture.